Editorial - Osgood, Jayne; Andersen, Camilla Eline; Angell, Mona-Lisa; Otterstad, Ann Merete (Reconceptualizing Educational Research Methodology, 2024)
This issue of RERM includes four papers that boldly attempt to propose ways in which educational research practices, traditions and methods might be enacted differently. They take seemingly foundational research methods (reviewing literature, ethnographic observation, walking methodologies) and transform them in to something less familiar that invite our readers to stutter and reappraise how else research might be done and with what outcomes. Firstly, researching from Danish inner cities, Staunæs and Vertelyte draw on affect theory and a concern with moods and felt pedagogies in education to explore how hopes and anxieties are woven through school objects and architecture. Through minor interventions the authors propose that there are abundant possibilities to improve the inclusion of racialized students in the inbetween, and often pathologised spaces of school. This holds the potential to radically shift perceptions, prejudices and behaviours that are not always identifiable but that can be sensed through the minor gesture. The authors attend to the significance of language and what happens through translation and diffractive readings. They stress that concepts that travel require careful consideration when transposed into alternative geopolitical contexts. They take Ahmed’s ‘happy objects’ as a case in point to make visible the specificities of local context and what that means for advancing theory that can pay closer attention to time and space. The next two papers address ways in which literature reviews – a staple element to any research project – can be up-ended and reimagined when post-foundational theories and practices are put to work. Naomi Pears-Scown makes use of Baradian theoretical concepts to think-with literature rather than merely review what is already known and organize a corpus of knowledge into useful categories. Through literature cartographies, Pears-Scown develops a mapping strategy that makes visible her affective engagement with literature through the crafting of found-poems which tell stories of the ways in which place shapes approaches to arts therapy in various geopolitical contexts. This novel approach to engaging with and encountering literature disrupts received wisdom about how literature should be reviewed and instead invites the reader to sit with the discomforts of expanding how literature stories can be told. In resonance with Pears-Scown, the next paper written by co-authors Boks-Vlemmix and Aspfors, offers a similar challenge to orthodoxies surrounding what a literature review is and how it should be undertaken. In their experimental piece the authors offer glimpses into what gets generated when the emphasis concerns processes and practices of doing a literature review rather than what it represents. Like the previous paper, the authors are inspired by a cartographic approach that holds the potential to map the processes involved in becoming deeply immersed and affect with a body of literature. They take literature on Teacher Educator Professional Learning as a case in point to explore how mapping and tracing entangled concepts can generate unanticipated insights and present new lines of thought. Finally, Louisa Allen explores the potential of smell, with all the senses and beyond the human, for educational research. She takes the reader on ‘smellwalks’ which presented themselves as an unlikely research method during pandemic lockdown. Allen provides detailed accounts of the ways in which smellwalks came into being in a small coastal town in Aotearoa-New Zealand and enabled a deep exploration of pandemic-transformed life at a daily and local level. The paper offers a theoretical examination of smellwalk methodology as a means to consider smell through multisensory conceptualisations where human senses are understood as distinct but overlapping. Further, the paper theorises the act of smelling as unbounded and ultimately, always more-than-human. A series of research moments are examined to demonstrate how smelling involves a multisensory experience that emerges with/through the material landscape. Together these papers offer important ways to reappraise approaches to research methodology in education that have become so deeply embedded that they unwittingly shape conventional expectations of how research should be done, has always be done. Each of these papers offer exciting invitations to interrupt this routine way of thinking. Respond to the invitation to pause, to ask, must we do it that way? The way it has always been done? What happens if we question and dare to experiment with alternative approaches? When theory is mobilized through research that seeks to pursue alternative lines of inquiry, what then? When theoretical concepts are taken up in/to ‘foreign’ spaces what happens to them? How do they travel? What do they agitate? What do they make possible? Aligned with the aims of this journal, these papers individually and collectively, invite a pause to business-as-usual in educational research. Jayne Osgood Camilla Andersen Mona-Lisa Angell Ann Merete Otterstad Editors